Household wastes: Disciplining the family in the name of austerity. Issue 4 (December 2016) - Cameron, Angus; Smith, Nicola; Tepe-Belfrage, Daniela
Abstract There is a substantial body of scholarship on the role of discourses in producing the neoliberal politics of austerity, but this has tended to leave untouched the question of how the household might be implicated in such discourses. This article argues that the introduction of various austerity programmes in the aftermath of the financial upheavals of 2008–2009 has produced a new normalisation of the British household, and that much of this centres on particular narratives surrounding the concept of waste. Offering a genealogy of waste, we contend that the language and very politics of austerity are in part made possible through longstanding, historic discourses of household waste, and yet the concept of waste is in itself being reconfigured and reimagined in and through the language of austerity. We argue that such discourses serve to naturalise the systemic inequalities and structural violences of neoliberal capitalism, for they render the poor both individually culpable for their own poverty and collectively culpable for Britain's economic and social crisis.